The Effect of Project Based Learning Model on Students’ Critical Thinking Ability in Economics Learning - Parida; Yeyen Suryani (Yayasan Dekhalisha Global Prestise, 2025)
Critical thinking ability is an essential skill in 21st century education, because it helps students to analyze, evaluate, and synthesize information logically for problem solving. The research used quasi-experiment method with pretest-posttest control group design. This study aims to test the effectiveness of the Project Based Learning learning model in improving the critical thinking skills of 11th grade students of SMA Negeri 3 Kuningan on inflation material. The results showed that students who studied using the Project Based Learning model experienced a higher increase in critical thinking skills than students in the control class. Although the increase was not statistically significant, the application of the Project Based Learning model proved to be able to encourage students to think more actively, collaborate, and analyze economic data contextually. Therefore, the Project Based Learning model has the potential to be an effective learning approach in developing students' critical thinking skills if implemented with more optimal planning and assistance.